Study the properties of dense Hydroxyapatite - Extract from cow bone - Sri Asliza, Md Amin; Mohd Zaheruddin, Kasmuin; Shahrizal, H.; Nurul Fazliana, Z. A (Malaysian Institute for Nuclear Technology Research, 2011)
Link to publisher's homepage at http://www.nuklearmalaysia.org/